2007
DOI: 10.1002/cmr.a.20094
|View full text |Cite
|
Sign up to set email alerts
|

Physical foundations, models, and methods of diffusion magnetic resonance imaging of the brain: A review

Abstract: ABSTRACT:The foundations and characteristics of models and methods used in diffusion magnetic resonance imaging, with particular reference to in vivo brain imaging, are reviewed.The first section introduces Fick's laws, propagators, and the relationship between tissue microstructure and the statistical properties of diffusion of water molecules. The second section introduces the diffusion-weighted signal in terms of diffusion of magnetization (Bloch-Torrey equation) and of spin-bearing particles (cumulant expa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 81 publications
2
92
0
2
Order By: Relevance
“…Our DTI results demonstrate AS-related changes in microstructural organization, consistent with reduced axonal density or myelination, 49 in the CC, cingulum, and CR, as inconsistently reported in previous literature, [32][33][34][35][36][37] selectively in males but not in females. Studies of patients with callosal agenesis have demonstrated that reduced interhemispheric connectivity, in addition to impacting intelligence quotient intellect and information integration, may lead to specific emotional and social deficits resembling those typical of ASCs.…”
Section: Discussionsupporting
confidence: 87%
“…Our DTI results demonstrate AS-related changes in microstructural organization, consistent with reduced axonal density or myelination, 49 in the CC, cingulum, and CR, as inconsistently reported in previous literature, [32][33][34][35][36][37] selectively in males but not in females. Studies of patients with callosal agenesis have demonstrated that reduced interhemispheric connectivity, in addition to impacting intelligence quotient intellect and information integration, may lead to specific emotional and social deficits resembling those typical of ASCs.…”
Section: Discussionsupporting
confidence: 87%
“…Several models, in particular the biexponential and diffusional kurtosis models, have been proposed [1,2]. A review can be found in [3].…”
Section: Introductionmentioning
confidence: 99%
“…The orthogonal effects are, however, often overlooked, since their strength is typically small in comparison to the diffusion-weighting gradients, and using the b-factor (b = B 11 + B 22 + B 33 ) greatly simplifies calculations (reference 44 in [27]). …”
Section: The Bloch-torrey Equationsmentioning
confidence: 99%
“…For the sake of simplicity let us also assume at first without loss of generality that the gradients are applied along the xaxis and that g denotes only the magnitude of the gradient vector (Fig-2.1) [27]. The dephasing resulting from the two gradient pulses is then inria-00496858, version 1 -1 Jul 2010…”
Section: The Fourier Relationshipmentioning
confidence: 99%
See 1 more Smart Citation